GREEN ACCOUNTING DAN DEKOMPOSISI NET PRESENT VALUE (NPV): INTEGRASI MANFAAT EKONOMI DAN LINGKUNGAN PADA PROYEK DEKARBONISASI GAS FLARING - Devia Septyani; M. Ikbal Aziz; Maya Matofani (CV. Lafadz Jaya, 2026)
This study aims to integrate the concept of green accounting with a Net Present Value (NPV) decomposition analysis on a gas flare decarbonization project at SP X, in order to identify the extent to which each environmental economic benefit source contributes to the project's overall investment value. Prior evaluations of this project generally report NPV, IRR, PBP, and MACC as aggregate indicators without explaining the proportional contribution of each benefit component — fuel saving, flare monetization, and carbon revenue — to the resulting NPV. This research applies a quantitative case-study approach using 2024–2025 operational data and a proportional-contribution NPV decomposition method. The results show that of the project's total NPV of USD 1,875,537.44, fuel saving is the dominant contributor at USD 1,462,099.59 (77.96%), followed by flare monetization at USD 293,535.24 (15.65%), and carbon revenue at USD 119,902.61 (6.39%). The project also achieves a net emission reduction of 57,599.99 tons of CO², a 96% IRR, a 2.9-month payback period, and a negative MACC of (USD 22,635.01) per ton of CO². The NPV decomposition demonstrates that operational efficiency from diesel savings is the primary driver of financial feasibility, while carbon revenue functions as a strategic add-on that reinforces environmental legitimacy without being the main determinant of profitability. These findings offer a new framework for oil and gas management in prioritizing decarbonization investments based on the real economic contribution of each benefit source.